Encrusting cystitis caused by Corynebacterium urealyticum - O. Yu. Nesterova; V. K. Dzitiev; N. I. Sorokin; A. A. Strigunov; I. A. Zhestkov; A. G. Korobova; A. V. Kadrev; R. M. Gorbunov; D. A. Filatova; A. A. Kamalov (Вестник урологии)
Incrusting cystitis is an extremely uncommon form of chronic bladder inflammation. It is characterised by wall calcification and associated with urease-producing microorganisms, most commonly Corynebacterium urealyticum. The enzyme urease triggers a cascade of urea cleavage into carbon dioxide and ammonia, thereby leading to hyperammoniuria and urine alkalisation within the first 24 hours. These conditions result in hypersaturation favourable for the formation of struvite and apatite crystals encrusting the bladder wall. The most significant predisposing conditions and risk factors for the development of encrusting cystitis are foreign bodies in the urinary system, such as urethral catheter, nephrostomy tube, internal ureteral stents. Additionally, a history of endoscopic surgery on the urinary tract is of special importance. This article presents a clinical case of successful treatment of encrusting cystitis in a man after transurethral resection of the prostate.